(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The Late Jurassic-Early Cretaceous Apulia platform margin and the transition to adjacent basinal deposits (inner platform to basin) are well exposed in the Gargano Promontory. Detailed field work has allowed to recognize eight main facies associations which reflect various depositional environments, and which document a differentiated zonation, from the inner platform to the basin. A shallow lagoon existed in the internal part of the Gargano Promontory with a transition to tidal flat areas (F1). Oolitic shoals (F2) bordered this internal peritidal area passing seaward to a reef-flat with abundant corals (F3). A reef-front, associated with a coral rubble zone, has been found in some areas (F4). In the external margin zone, massive wackestones with Ellipsactinia occur (F5) and pass gradually to a rudstone facies on the proximal slope (F6). The base-of-slope facies association consists of pelagic sediments interbedded with gravity-displaced deposits (F7 and F8). The depositional profile of the Apulia Platform is typical of the Tethyan Jurassic-Early Cretaceous platforms, with slope declivities in the order of 25°-28°. The remarkable progradation of the platform in the northern tract of the Gargano (Lesina and Varano lakes area) and its substantial stability east- and southwards (Mattinata area) suggest a possible windward position of the margin in this latter portion and, in contrast, a leeward position of the northern portion.